«… Constant wonder of God» - Irina Kovaleva; Nataliya Tyagunova (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This publication is devoted to the memoirs of the nun of Serafi mo-Znamensky Skete of Moscow diocese Veronica (Sokolikova), which for more than half a century have been kept in the personal archive of Krivolutsky family. Priest Vladimir Krivolutsky recorded memoirs of nun Veronica, and his son gave the manuscript to the archives of St. Tikhon’s University. Being a record of an oral story, the memoirs abound with information which is not found in any of the known sources that cover the history of this monastery and the life of nun Tamar (Mardzhanova; Russ. Фамарь Марджанова). The memoirs of the 1920–1930s about Serafi mo-Znamensky Skete, about mother superior Tamar, the nuns, the clergy who served in the churches of the monastery, about bishop Arseniy (Zhadanovsky), who was for many years spiritual father of the sisters of the Skete, were created in conditions of severe persecution of the Russian Orthodox Church, arrests, searches and repressions and, as a rule, do not include any mention of specific individuals or the chronology of the events. However, this document is valuable and fi lls gaps in the historiography of this period. Many of the facts mentioned in the publication fi nd an almost literal confi rmation in documents of historical and specialised archives, which makes it possible to regard this source as reliable.